Design and analysis of Hollow-core fiber with anti-resonant structure for Ethylene detection. Issue 1 (1st January 2023) - Joonmasaa, Kwanjira; Sangtawesin, Sorawis; Meemon, Panomsak; Talataisong, Wanvisa
Abstract: An optical fiber for mid-infrared (mid-IR) guidance has long attracted great interest due to its wide range of applications especially in gas sensing. Ethylene gas is one of an important gas, which release from the fruit and flower, owing to their ripening process. Thus, the controlling and detection of ethylene gas is of interest for the storage and exportation of fruits and flowers. Gas detection using the hollow-core optical fiber (HCF) is a promising technique due to it intrinsic micro-channel structure that allows the gas to flow through the HCF for detection propose. Here, a hollow-core anti-resonant fiber (HC-ARF) is designed and optimized for mid-IR guidance for the purpose of ethylene detection. The HC-ARF includes 6 inner tubes which is optimized to achieve a low confinement loss at a wavelength of 3.2 µm (ethylene absorption wavelength). The simulation result shows that a confinement loss of 2 dB/m at the wavelength of 3.2 µm can be achieved when the fiber core diameter is 128 µm and the thickness and the diameter of inner tubes are 2 µm and 92 µm, respectively.